Risk Stratification in COVID-19 Pneumonia – Determining the Role of Lung Ultrasound - Tombini, Valeria; Di Capua, Mirko; Capsoni, Nicolò; Lazzati, Andrea; Bergamaschi, Marta; Gheda, Silvia; Ghezzi, Leonardo; Cassano, Giulio; Albertini, Valentina; Porta, Lorenzo; Zacchino, Massimo; Campanella, Carlo; Guarnieri, Linda; Cazzola, Katia Barbara; Velati, Marta; Di Domenico, Sandro Luigi; Tonani, Michela; Spina, Maria Teresa; Paglia, Stefano; Bellone, Andrea (Ultraschall in der Medizin - European Journal of Ultrasound, 2021)
LUS patterns of COVID-19 pneumonia have been described and shown to be characteristic. The aim of the study was to predict the prognosis of patients with COVID-19 pneumonia, using a score based on LUS findings.Materials and Methods An observational, retrospective study was conducted on patients admitted to Niguarda hospital with a diagnosis of COVID-19 pneumonia during the period of a month, from March 2nd to April 3rd 2020. Demographics, clinical, laboratory, and radiological findings were collected. LUS was performed in all patients. The chest was divided into 12 areas. The LUS report was drafted using a score from 0 to 3 with 0 corresponding to A pattern, 1 corresponding to well separated vertical artifacts (B lines), 2 corresponding to white lung and small consolidations, 3 corresponding to wide consolidations. The total score results from the sum of the scores for each area. The primary outcome was endotracheal intubation, no active further management, or death. The secondary outcome was discharge from the emergency room (ER).Results 255 patients were enrolled. 93.7 % had a positive LUS. ETI was performed in 43 patients, and 24 received a DNI order. The general mortality rate was 15.7 %. Male sex (OR 3.04, p = 0.014), cardiovascular disease and hypertension (OR 2.75, p = 0.006), P/F (OR 0.99, p < 0.001) and an LUS score > 20 (OR 2.52, p = 0.046) were independent risk factors associated with the primary outcome. Receiver operating characteristic (ROC) curve analysis for an LUS score > 20 was performed with an AUC of 0.837. Independent risk factors associated with the secondary outcome were age (OR 0.96, p = 0.073), BMI (OR 0.87, p = 0,13), P/F (OR 1.03, p < 0.001), and LUS score < 10 (OR 20.9, p = 0.006). ROC curve analysis was performed using an LUS score < 10 with an AUC 0.967.Conclusion The extent of lung abnormalities evaluated by LUS score is a predictor of a worse outcome, ETI, or death. Moreover, the LUS score could be an additional tool for the safe discharge of patient from the ER.
Keywords: chest; point of care; echocardiography